Imaging skeletal muscle volume, density, and FDG uptake before and after induction therapy for non-small cell lung cancer. Issue 5 (May 2018) - Goncalves, M.D.; Taylor, S.; Halpenny, D.F.; Schwitzer, E.; Gandelman, S.; Jackson, J.; Lukose, A.; Plodkowski, A.J.; Tan, K.S.; Dunphy, M.; Jones, L.W.; Downey, R.J.
Abstract : Aim: To assess whether changes in body composition could be assessed serially using conventional thoracic computed tomography (CT) and positron-emission tomography (PET)/CT imaging in patients receiving induction chemotherapy for non-small cell lung cancer (NSCLC). Materials and methods: CT-based skeletal muscle volume and density were measured retrospectively from thoracic and lumbar segment CT images from 88 patients with newly diagnosed and untreated NSCLC before and after induction chemotherapy. Skeletal muscle 2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG) uptake was measured from PET/CT images from a subset of patients ( n =42). Comparisons of each metric before and after induction chemotherapy were conducted using the non-parametric Wilcoxon signed-rank test for paired data. The association between clinical factors and percentage change in muscle volume was examined using univariate linear regression models, with adjustment for baseline muscle volume. Results: Following induction chemotherapy, thoracic (–3.3%, p =0.0005) and lumbar (–2.6%, p =0.0101) skeletal muscle volume were reduced (adiposity remained unchanged). The proportion of skeletal muscle with a density <0 HU increased (7.9%, p <0.0001), reflecting a decrease in skeletal muscle density and skeletal muscle FDG uptake increased (10.4–31%, p <0.05). No imaging biomarkers were correlated with overall survival. Conclusion: Changes in body composition can be measured from routine thoracic imaging. During chemotherapy skeletal muscle volume and metabolism are altered; however, there was no impact on survival in this retrospective series, and further validation in prospective, well-controlled studies are required. Highlights: Weight loss is common and predictive in patients with NSCLC; however, the composition of this lost weight is unknown. Standard of care imaging can identify changes in muscle volume, density, and FDG uptake during cancer therapy. Skeletal muscle volume, density, and metabolism change during treatment; the clinical significance requires further study.